Investigation of the structural, optical and gas sensing properties of PANI coated Cu–ZnS microsphere composite. Issue 45 (15th July 2020) - Parangusan, Hemalatha; Bhadra, Jolly; Ahmad, Zubair; Mallick, Shoaib; Touati, Farid; Al-Thani, Noora
Abstract : Polyaniline (PANI)/Cu–ZnS composites with porous microspheres are prepared by a hydrothermal and in situ polymerization method. Abstract : Polyaniline (PANI)/Cu–ZnS composites with porous microspheres are prepared by a hydrothermal and in situ polymerization method. The structural, optical, and morphological properties are characterized by X-ray powder diffraction, FTIR, UV-vis, scanning electron microscope, transmission electron microscope. The XRD results confirmed that the PANI/Cu–ZnS composite is formed. The morphological analyses exhibited that the PANI/Cu–ZnS composite comprises the porous microspherical structures. The emission peaks obtained in photoluminescence spectra confirm the presence of surface defects in the prepared composite. The UV-DRS study shows that the bandgap of the samples is found to decrease for the PANI/Cu–ZnS composite compared to the pure Cu–ZnS sample. The calculated band gap ( E g ) value of PANI/Cu–ZnS composite is 2.47 eV. Furthermore, the fabricated gas sensor based on PANI/Cu–ZnS can perform at room temperature and exhibits good gas sensing performance toward CO2 gas. In particular, PANI/Cu–ZnS sensor shows good response (31 s) and recovery time (23 s) upon exposure to CO2 gas. The p/n heterojunction, surface defects, and porous nature of the PANI/Cu–ZnS composite microsphere enhanced sensor performance.